The Wire og kriminalitetens afkroge - Andersson, Robert; Bruhn, Jørgen; Gjelsvik, Anne (Passage - Tidsskrift for litteratur og kritik, 2012)
Robert Andersson, Jørgen Bruhn og Anne Gjelsvik: "The Wire og kriminalitetens afkroge" Abstract Robert Andersson, Jørgen Bruhn & Anne Gjelsvik: “The Wire and the Corners of Crime” This article argues that the American TV-series The Wire poses complicated political and ideological questions rather than attempting to deliver clear-cut answers or solutions to the problems represented. The Wire is analysed both as an aesthetic phenomenon (narratological and thematic analysis) and as a representation of societal elements (which demands analysis based on sociological, historical and criminological perspectives). After a brief overview of the series, the authors aim to generalise the results of the analysis of a particular part of the five-season series, namely the “Hamsterdam-episode”.